2006
DOI: 10.1021/ol060130y
|View full text |Cite
|
Sign up to set email alerts
|

Chemically Modified Dansyl Probes: A Fluorescent Diagnostic for Ion and Proton Detection in Solution and in Polymers

Abstract: [reaction: see text] The fluorescence emission intensity of the dansyl group is significantly diminished upon appending an ethyldimethylamino group to the N1 nitrogen substituent. Addition of acids and metal ions (i.e., Zn(2+)) to solutions of trimethylethylenediamine naphthalene sulfonamide (trinsyl) 2 produces a >25-fold increase in fluorescence intensity. Trinsyl probe 2 has been used as a diagnostic for the diffusion of protons and metal ions in a network polymer as well as an optical reporter for the glas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(17 citation statements)
references
References 37 publications
1
16
0
Order By: Relevance
“…The influence of pH on the fluorescence detection of D‐P5 to Hg 2+ and Cu 2+ was measured, as shown in Figure . Results indicated that D‐P5, D‐P5‐Hg and D‐P5‐Cu showed a weak fluorescence intensity in acidic solution (pH < 4) that could be attributed to charge transfer between the dimethylamino group and napthyl moiety and was prevented by the protonated dimethylamino group (pK a ~4) of fluorophore dansyl chloride . However, a weakly alkaline environment had less influence on these fluorescence peaks.…”
Section: Resultsmentioning
confidence: 96%
“…The influence of pH on the fluorescence detection of D‐P5 to Hg 2+ and Cu 2+ was measured, as shown in Figure . Results indicated that D‐P5, D‐P5‐Hg and D‐P5‐Cu showed a weak fluorescence intensity in acidic solution (pH < 4) that could be attributed to charge transfer between the dimethylamino group and napthyl moiety and was prevented by the protonated dimethylamino group (pK a ~4) of fluorophore dansyl chloride . However, a weakly alkaline environment had less influence on these fluorescence peaks.…”
Section: Resultsmentioning
confidence: 96%
“…The unusual four-membered coordination ring motif proposed for the mono-Cd 2 þ complex has been identified in an X-ray crystal structure of a 1,8-naphthyridine -Ir(III) complex (107). However, the acyclic, mono-or dinuclear complexes (see below) of various transition metals (Ru (108), Cu, Ni, Zn, Co (114)(115)(116) reduced the rate of PET. Upon coordinating the first Cd 2 þ to form the proposed mononuclear complex, the HOMO of the fluorophore is lowered to afford a more efficient PET process, which results in fluorescence quenching.…”
Section: Group 2: Ligands Capable Of Forming Both Monoand Dinuclear Cmentioning
confidence: 96%
“…This can be described by considering that a classical on-off probe (from acidic to neutral-basic pH) has been converted to an off-on probe for the same pH modification. 25 The fluorescence emission maximum of the dansyl chromophore of 3 in an aqueous solution (Fig. S12 † for pH titration).…”
Section: Acid-base Titration Of Compoundmentioning
confidence: 99%